Emulsion gels in food systems: advances, oxidative stability challenges, and mitigation - Dai, Wen; Xiong, Huihui; Sun, Wenhui; Zhou, Cuicui; Tan, Chin Ping; Li, Bo; Xu, Yong Jiang (Taylor and Francis, 2025)
Emulsion gel that composed of water, oil, emulsifier, gelling agent and other substances has been widely used in the field of food science, such as encapsulant and delivery of active compounds, fat substitutes and plastic materials. The application of emulsion gels is primarily constrained by physical and oxidative stability. However, in the field of food research, the focus is typically on preserving the physical stability of emulsion gels. The oxidation stability, which is relevant to human health, has been largely overlooked. Currently, research on the oxidation of emulsion gels remains insufficient, with a lack of systematic evaluation methods and effective countermeasures. Consequently, this review offers a comprehensive overview of the the preparation and application of emulsion gels, along with an examination of their oxidative and oxidative stability. In this process, the assessment methods were discussed, and the factors influencing the oxidation of emulsion gels, including composition, preparation methods, and interfacial factors, were reviewed. Preventive measures were also proposed. This article calls for future research to focus on the development of novel antioxidant systems for emulsion gels, optimization of preparation processes, and enhancement of material stability to promote the sustainable development of emulsion gel technology.